2016
DOI: 10.1007/s11069-015-2141-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of droughts in Romania using the Standardized Precipitation Index

Abstract: 29This paper analyses the temporal and spatial variability of droughts in Romania, over the last five 30 decades, based on a high-resolution data set developed at country level, namely ROCADA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 34 publications
4
47
0
Order By: Relevance
“…The drought episode of 2000/2001 was identified as the most severe in the study area in the period 1960-2013 (Spinoni et al, 2013;Ionita et al, 2016), and its spatial coverage reached 60% of Romania (Ionita et al, 2016). Our results also show vegetation under stress conditions on most of the study area, and on roughly 70% of the area these stress conditions lasted 4 or more months.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The drought episode of 2000/2001 was identified as the most severe in the study area in the period 1960-2013 (Spinoni et al, 2013;Ionita et al, 2016), and its spatial coverage reached 60% of Romania (Ionita et al, 2016). Our results also show vegetation under stress conditions on most of the study area, and on roughly 70% of the area these stress conditions lasted 4 or more months.…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless, the drought episode of 2000/2001 was identified as the most severe in the period 1960-2013 (Spinoni et al, 2013, Ionita et al 2016. Using 6-months SPI and SPEI, Spinoni et al (2013) …”
Section: Drought Episode Of 2000/2001mentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, PDSI and SPI used for meteorological drought monitoring, CMI for agricultural drought, SRI for hydrological drought, and DSI for regional drought (Narasimhan and Srinivasan 2005;Dai 2011;Mukherjee et al 2018). However, SPI is one of the common indices for detecting drought on a different scale (i.e., 1, 3, 6, 9, 12 months); which is widely used in many countries such as Romania (Ionita et al 2016); Ethiopia (El Kenawy et al 2016); Italy (Bonaccorso et al 2015); Syria (Mohammed et al 2019b), India (Dutta et al 2015), Poland (Łabędzki 2007); China (Zhang et al 2009), Hungary (Mohammed and Harsányi 2019); Greece (Livada and Assimakopoulos 2007); USA (Hayes et al 1999), and many other parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (Busuioc et al, 2014;Rîmbu et al, 2014;Bîrsan et al, 2014;Cheval et al, 2014;Ionita et al, 2016) have convincingly shown that the region is experienced a continuous warming and drying trend in the past decades, both during winter and summer, that have also affected rivers' discharge (Ionita et al 2015a;Ionita, 2015). Changing climate can affect the water balance of river catchments, via changes in precipitation (which affect the river runoff) and via increased temperatures which lead to increased 20 evapotranspiration, as well as melting of the glaciers and changes in the timing and amount of snow fall and snow melt.…”
Section: Introductionmentioning
confidence: 99%